IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXTS THROUGH DICTOGLOSS TECHNIQUE - Oktavianda, Melti; Rufinus, Albert; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Penelitianiniadalahpenelitiantindakankelaspadasiswakelas VIIISekolahMenengahPertamaNegeri 10 Pontianak di tahunakademik 2012/2013. Penelitianinibertujuanuntukmeningkatkankemampuansiswadalammenulisceritateks narrative.Dalampenelitianini, teknikDictoglossdigunakansebagaistrategiuntukmembantusiswadalammenulisteks narrative.ProsesdariteknikDictogloss di penelitianiniterdiridaripersiapan, dikte, diskusi, rekonstruksi, analisis, dankoreksi.Teknikpengumpulan data yang digunakanmeliputilembarobservasi, catatanlapanganuntukmencatat proses kegiatan di dalamkelas; dantesmenulisuntukmengukurkemampuansiswadalammenulisteks narrative.Hasil data penelitiandianalisisberdasarkanrubrikpenilaian.Kemampuansiswadalammenulisteks narrativemengalamipeningkatanpadatigasiklusdari 67,23padasikluspertama, kemudianmeningkatmenjadi 72,86padasikluskeduadanmencapai 80,11 padasiklusketiga. TeknikDictoglossdapatmembantusiswameningkatkkankemampuanmenulisteks narrative Kata kunci: kemampuanmenulis, teknikdictogloss, penelitiantindakan kelas, teks narrative. Abstract: This study was a classroom action research (CAR) to the eighth grade students of SMP Negeri 10 Pontianak in academic year 2012/2013. The purpose of this research was to improve their ability in writing narrative texts. In this study, Dictogloss technique was used as a strategy to help students in writing narrative texts. The processes of Dictogloss technique in this research were preparation, dictation, discussion, reconstruction, analysis and correction. The techniques of data collecting in this research were observation checklists and field notes to record the process in the classroom; and written test to measure the students’ ability in writing narrative text.Data was analyzed by using scoring profile. The students’ writing ability in narrative texts improved in three cycles from 67,23 in cycle 1, then improved to 72,86 in cycle 2 and improved to 80,11 in cycle 3. In conclusion, the Dictogloss technique can help the students improve their writing ability on narrative text and using simple past tense correctly. Keywords: writing ability, dictogloss technique, classroom action research, narrative texts.